Student perceptions of faculty caring in online nursing education: A mixed-methods study. (May 2022) - Jones, Kate; Polyakova-Norwood, Vera; Raynor, Phyllis; Tavakoli, Abbas
Abstract: Background: As the prevalence of online nursing education increased, so did the need for faculty to understand student perceptions of faculty behaviors that demonstrate caring and promote student success. Literature from both education and nursing journals supported this study. Objectives: Primary objectives were to identify how the value of caring is made visible in online learning, to understand how students prioritized faculty caring behaviors and to identify any significant differences in perceptions related to student demographics. A secondary objective was to provide professional development tools for faculty who teach nursing students in the online environment. Design: Mixed methods. Setting: A College of Nursing within a large public university in the Southeastern United States. Participants: One hundred and forty-one (141) nursing students pursuing graduate degrees (MSN or DNP) participated in the student survey and 15 participated in the focus groups/interviews; 28 faculty members responded to the survey. Methods: A validated survey tool was used to identify how students prioritized faculty caring behaviors. Facilitator-led focus groups were used to gain additional insights. Faculty members were surveyed to compare faculty and student priorities. Descriptive and correlational analyses were performed. Results: Graduate nursing students perceived a course that is well-designed, with clear instructions and communication, and a supportive environment, to be evidence of faculty caring. There were significant differences in student responses when analyzed by demographic characteristics such as gender and race. Student perceptions aligned with previous research on this topic; faculty and student perceptions differed in some areas. Conclusion: Quantifying graduate student perceptions about faculty caring behaviors provided information that is used for faculty professional development. Further research is needed to explore perceptions of faculty caring in different student populations. Multi-site studies to explore race and gender differences in perception are also recommended. Highlights: Caring is central to nursing and to online nursing education. Faculty caring behaviors start with intentional course design elements. Race and gender differences are noted when students rank caring behaviors. Students and faculty prioritize certain behaviors differently. Further research should explore implications for course design and delivery.